Pengaruh Arang Sekam Padi Terhadap Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium ascolanicum.L) - Handayani, Rizky; Lufita Nur Alfiah; Rizah Rizwana Wahyuni (Universitas Pasir Pengaraian, 2024)
RIZKI HANDAYANI, NIM 1827028.